Physicochemical characterization of biodegradable polymer polyhydroxybutyrate from halophilic bacterium local strain Halomonas elongata - W.O.S. Rizki; E. Ratnaningsih; D.G.T. Andini; S. Komariah; A.T. Simbara; R. Hertadi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Petroleum-based plastics produce tremendous amounts of plastic waste every year, which contributes to environmental problems. Biological polymers, such as polyhydroxybutyrate, have caught attention as an ecofriendly substitute to petroleum-based plastics. The present study focused on the production, enhancement, and characterization of polyhydroxybutyrate from the prospective local bacterium Halomonas elongata. This research aimed to develop an environmentally sustainable material for reducing the accumulation of plastic waste in the ecosystem.METHODS: A local bacterial strain from Mud Crater Bledug Kuwu, Grobogan, Central Java, Indonesia, was isolated and identified as Halomonas elongata. Nile red staining method confirmed that this bacterium accumulated polyhydroxybutyrate. The effect of incubation time, sodium chloride concentration, nitrogen, and carbon sources were evaluated via gas chromatography to enhance its productivity. The functional groups of isolated polyhydroxybutyrate were analyzed using nuclear magnetic resonance and Fourier transform infrared spectroscopy. Morphology and composition were demonstrated by scanning electron microscopy and energy-dispersive x-ray spectroscopy. Thermogravimetric analysis, differential thermogravimetry, and differential thermal analysis were used to analyze thermal stability.FINDINGS: Halomonas elongata produced polyhydroxybutyrate utilizing glucose as a carbon source, as evidenced by orange-fluorescence colonies under ultraviolet light. The optimum condition of polyhydroxybutyrate production was achieved when the bacterium was cultivated in a high medium containing 5 percent sodium chloride, 0.2 percent yeast extract, and 5 percent glucose (as measured by weight per volume) after 72 hours of incubation. The maximum polyhydroxybutyrate production in this medium reached 2.93 ± 0.03 gram per liter dry cell weight and 78 ± 1 percent polyhydroxybutyrate concentration. Structural elucidation studies revealed that the biopolymer produced by this bacterium was high-purity polyhydroxybutyrate, as proven by the presence of functional groups and proton resonance signals in the monomer structure. The isolated polyhydroxybutyrate consisted of 14 percent carbon and 86 percent oxygen. Thermal stability analysis showed that the isolated polyhydroxybutyrate had a maximum decomposition temperature of 270 degrees Celsius. Micrographically, the isolated polyhydroxybutyrate appeared as a sheet structure with interconnected fibers measuring 0.7–0.8 micromter in length. This finding also demonstrates that the isolated polyhydroxybutyrate has good thermal stability given that fibers linked each polyhydroxybutyrate molecule, which boosted the structure of polyhydroxybutyrate.CONCLUSION: This study successfully synthesized polyhydroxybutyrate using a local strain of Halomonas elongata, with glucose as a carbon source. Physicochemical characterization revealed that polyhydroxybutyrate from this bacterium has a high thermal stability. The yield of polyhydroxybutyrate can be increased through the improvement of production parameters. This research emphasizes an important milestone toward the large-scale production of polyhydroxybutyrate for application as food packaging while reducing environmental issues.